Researching the Blocking of Current Protection of Electrical Power Units with Transformers - F. A. Romaniuk; V. Yu. Rumiantsev; Yu. V. Rumiantsev; A. A. Dziaruhina; P. I. Klimkovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The magnetizing current inrush appears in electrical power units equipped with transformers in case of no-load energizing of the power transformers and in a number of other cases. This phenomenon could cause a false triggering of the current protection. To prevent incorrect actions of the current protection during the magnetizing current inrush a protection blocking is carrying out. The blocking principle operation is based on the fact that in a three-phase system in normal mode and in case of symmetrical short circuit the first harmonics contained in the phase currents of electrical installations form a direct sequence and the second ones – the negative sequences. In case of an asymmetric mode, including an asymmetric short circuit, the negative sequence appears, formed by the first harmonics that are part of the phase currents of the specified system. In magnetizing current inrush modes, second harmonics of significant magnitude are present in phase currents, which form the negative sequence. Based on the analysis of the information parameters of the specified sequences currents, identification of the magnetizing current inrush and short-circuit modes is performed with the implementation of the protection blocking if necessary. The study of the current protection blocking functioning was performed using computational experiment by analyzing the calculated changes of blocking parameter compared with the threshold setpoint. The specified researching is done by using the digital model that is implemented in the dynamic modeling environment MatLab-Simulink. As a result of the performed calculations, the principal operability of the proposed current protection blocking was confirmed that provides a fairly reliable identification of the magnetizing current inrush and short-circuits modes, regardless of the degree of saturation of current transformers. It was found that the proposed principle of the current protection blocking has a higher sensitivity in comparison with the classical one based on the estimation of the ratio of the second and first harmonics of the phase currents. In short-circuit modes in an electrical power units the proposed blocking causes a current protection operation delay that can be reduced by digital filters performance improvement.